Examining Employee Turnover Intention in the Non-Sharia Financial Institution - Eko Tama Putra Saratian; Muhammad Jamaluddin; Tine Yuliantini; Tri Susilowati; Syarief Achmad (Journal of Finance and Business Digital, 2023)
This study aims to analyze the effect of work stress, work environment, and workload on employee turnover intention in the Conventional Financial Institution. The object of this research is employees on the Conventional Financial Institution in Jakarta. The sampling method used is a saturated sample of 30 respondents. The data collection method used a survey method with the research instrument being a questionnaire. The data analysis method uses the Partial Least Square (PLS) method with data processing through SmartPLS 3.0 software. The results of this study indicate that work stress has a positive and insignificant effect on turnover intention, the work environment has a negative and significant effect on turnover intention, and workload has a positive and significant effect on turnover intention.